Peran Pendidikan Multikutur dalam Membangun Bangsa yang Nasionalis dan Religius - Choirul Anwar; Roy Kulyawan (PIJAR: Jurnal Pendidikan dan Pengajaran, 2022)
This study aims to provide an overview of the role of multicultural education in building a nationalist and religious nation. The research method used is descriptive research based on experts or previous research and collecting data from several scientific journals and books. Indonesia is a very multicultural country, which can be seen from the many differences that exist within it. Differences are not something for us to be divided, but differences will make us remain strong and united in every diversity that exists. Indonesia has diversity, starting from the diversity of tribes, religions, languages ​​and cultures. Not only that, Indonesia also consists of 17,000 islands, which makes Indonesia famous for its natural wealth. However, there are various problems that must be faced by the Indonesian nation, starting from divisions resulting from differences in religion, ethnicity, and language. This is where the role of multicultural education is implemented in everyday life so that the Indonesian people can continue to unite in the diversity that exists